The Influence of Brand Image and Service Quality on User Satisfaction of Lion Parcel Services - Rr. Endang Wahyuni; Agus Setiawan; Malika Alya Kasta; Muhammad Edrian Jody (Dinasti Review, 2025)
Lion Parcel is a freight forwarding company that serves domestic and international shipments. The low quality of service in Lion Parcel can affect customer satisfaction and make customers switch to other service companies. This is a challenge for Lion Parcel to improve service quality to attract consumer buying interest. The aim of this study was to assess the effects of brand image and service quality on customer satisfaction of Lion Parcel services in Tugu Utara, Jakarta. A quantitative research approach was employed, utilizing questionnaries distributed to Lion Parcel customers. A probabilistic sampling method was applied, involving a sample of 85 individuals. The data collected was analyzed using linear regression to evaluate the influence of brand image and service quality on customer satisfaction. The results in this study are, service quality and Brand Image have a significant influence and on customer satisfaction.